Detestable and wicked arts : New England and witchcraft in the early modern Atlantic world - Moyer, Paul Benjamin, 1970- (Cornell University Press, 2020)
"While interpersonal, local, and regional contexts are critical to the analysis of witch-hunting in early New England, this book shows that a full understanding of the Puritan colonies' battle against black magic can only be achieved by placing it in a trans-Atlantic perspective"--